Analyzing the association of critical illness and cardioversion success in patients with atrial fibrillation at the emergency department - Sophie Gupta; Sebastian Schnaubelt; Julia Oppenauer; Martin Lutnik; Filippo Cacioppo; Alexander Spiel; Hans Domanovits; Patrick Sulzgruber; Jan Niederdöckl (Scientific Reports)
Abstract In critically ill patients with atrial fibrillation (AF), standard treatment algorithms might not be applicable. Emergency departments (ED) play a crucial role in implementing individualized treatment approaches. The aim of this study was to assess the association of lactate and cardioversion success rates in AF patients presenting to an ED. This was a retrospective single-center study analyzing 3535 AF episodes between 2012 and 2022. The main outcome was cardioversion (CV) to sinus rhythm (SR) depending on serum lactate levels (mmol/L). Lactate levels were divided into quintiles (lac < 1.1, 1.1–1.3, 1.4–1.7, 1.8–2.3 and > 2.3 mmol/L). Overall CV success declined with rising lactate levels (SR: lac < 1.1 79% (n = 547), 1.1–1.3 76% (n = 579), 1.4–1.7 73% (n = 562), 1.8–2.3 66% (n = 447), > 2.3 mmol/L 61% (n = 393); p < 0.001). Electrical CV (eCV) was conducted in 1021 (SR 95%), medical CV (mCV) in 706 (SR: 72%), facilitated CV in 523 (SR: 88%) and spontaneous conversion was observed in 591 (46% of all patients without treatment) cases. ECV was effective independent of lactate levels (SR: lac < 1.1 96% (n = 225), 1.1–1.3 93% (n = 253), 1.4–1.7 97% (n = 228), 1.8–2.3 92% (n = 154), > 2.3 mmol/L 95% (n = 106); p = 0.716). However, for mCV, conversion success decreased with increasing lactate levels (SR: lac < 1.1 84% (n = 95), 1.1–1.3 80% (n = 109), 1.4–1.7 75% (n = 115), 1.8–2.3 67% (n = 93), > 2.3 mmol/L 59% (n = 97); p < 0.001). Overall cardioversion success was less likely with rising lactate levels; especially medical cardioversion success rates decreased. Therefore, AF in critically ill may benefit from either electrical cardioversion, treatment of the underlying condition, or primary rate control.